Sex Differential in 15‐Hydroxyprostaglandin Dehydrogenase Levels in the Lumen of Human Intracranial Aneurysms. Issue 10 (17th October 2017) - Chalouhi, Nohra; Jabbour, Pascal; Zanaty, Mario; Starke, Robert M.; Torner, James; Nakagawa, Daichi; Hasan, David M.
Abstract : Background: Aspirin is a promising medical therapy for the prevention of intracranial aneurysm (IA) rupture. Recently, we found that men have a better response to aspirin than women. The purpose of this study was to determine whether a sex differential exists in the level of 15‐hydroxyprostaglandin dehydrogenase (15‐PGDH) in the lumen of human IAs. Methods and Results: Consecutive patients undergoing coiling or stent‐assisted coiling for a saccular IA at our institution were enrolled. Two samples (A and B) were collected from IA lumens, and the plasma level of 15‐PGDH was measured using an ELISA‐based method. The study included 38 patients, with 20 women and 18 men. Women and men were comparable on baseline characteristics. The mean plasma concentration of 15‐PGDH did not differ statistically between sample A (62.8±16.2 ng/mL) and sample B (61.8±17.9 ng/mL; 95% confidence interval −6.6 to 9.4). The mean plasma concentration of 15‐PGDH in IA lumens of samples A and B was significantly higher in men (73.8±13.5 ng/mL) than women (49.6±7.8 ng/mL; P <0.0001). Conclusions: Higher enzyme levels of 15‐PGDH exist in the lumen of IAs of men compared with women. This observation could explain why aspirin confers better protection against IA rupture in men than in women. The susceptibility of an individual to aspirin may differ according to the level of 15‐PGDH.